Anticoagulation efficacy of dabigatran etexilate for left atrial appendage thrombus in patients with atrial fibrillation by transthoracic and transesophageal echocardiography. Issue 26 (June 2018) - Xing, Xiao Fei; Liu, Nan Nan; Han, Ya Ling; Zhou, Wei Wei; Liang, Ming; Wang, Zu Lu
Abstract : Abstract: To evaluate the anticoagulation efficacy of dabigatran etexilate for left atrial appendage (LAA) thrombus resolution in patients with atrial fibrillation by transthoracic echocardiography and transesophageal echocardiography, and to investigate the anticoagulation factors. A total of 58 atrial fibrillation patients with LAA thrombus in our hospital were enrolled. After dabigatran etexilate anticoagulation for 3 months, the patients were divided into the effective group and ineffective group according to dissolution of thrombosis. The baseline data and the left atrial diameter (LAD), left atrial ejection fraction (LAEF), left ventricular ejection fraction, LAA flow velocity (LAA-v), and LAA thrombus size before and after anticoagulation treatment were recorded, and the measurement index were statistically analyzed. After the patients received anticoagulation treatment for 3 months, 15 patients had complete dissolution, thrombus in 21 patients reduced significantly, and the complete dissolution rate was 25.9% (15/58), the effective rate of dissolution was 62.1% (36/58). Compared with the ineffective group, the proportion of persistent atrial fibrillation and LAD in effective group were lower than those in the ineffective group, the LAEF and LAA-v in the effective group were higher than those in the ineffective group, and the differences were statistically significant ( P < .05). Multivariate logistic regression analysis on the baseline data and each ultrasound index showed that the type of atrial fibrillation, LAD, LAEF, and LAA-v were independently associated with the efficacy of anticoagulation ( P < .05). Dabigatran etexilate is effective in dissolution of LAA thrombus in patients with atrial fibrillation, and the atrial fibrillation type, LAD, LAEF, and LAA-v are significantly related with the efficacy of anticoagulation.